We need winners in the race to increase photosynthesis in rice, whether from conventional breeding, biotechnology or both. (7th October 2013) - LONG, STEPHEN P.
<x xml:space="preserve">Abstract</x> This article comments on: Can exploiting natural genetic variation in leaf photosynthesis contribute to increasing rice productivity? A simulation analysis